Peptidylarginine Deiminase 2 Autoantibodies Are Linked to Less Severe Disease in Multiple Sclerosis and Post-treatment Lyme Disease - Kim, Yaewon; Rebman, Alison W.; Johnson, Tory P.; Wang, Hong; Yang, Ting; Colantuoni, Carlo; Bhargava, Pavan; Levy, Michael; Calabresi, Peter A.; Aucott, John N.; Soloski, Mark J.; Darrah, Erika (Frontiers in Neurology, 2022)
Background: Peptidylarginine deiminase 2 (PAD2) mediates the post-translational conversion of arginine residues in proteins to citrullines and is highly expressed in the central nervous system (CNS). Dysregulated PAD2 activity has been implicated in the pathogenesis of several neurologic diseases, including multiple sclerosis (MS). In this study, we sought to define the cellular and regional expression of the gene encoding for PAD2 (i.e. PADI2) in human CNS tissue and evaluate whether anti-PAD2 antibodies were present in patients with various neurologic diseases. Methods: A total of 491 study participants were included in this study: 91 people with MS, 32 people with neuromyelitis optica (NMO), 281 people with post-treatment Lyme disease (PTLD), and 87 healthy controls. To measure PADI2 expression in the CNS from healthy individuals, publicly available tissue and single cell RNA sequencing data was analyzed. Anti-PAD2 antibodies were measured in the serum of study participants using anti-PAD2 ELISA. Clinical and demographic variables were compared according to anti-PAD2 antibody positivity for the MS and PTLD groups and correlations between anti-PAD2 levels and disease severity were examined. Results: PADI2 expression was highest in oligodendrocytes (mean ± SD; 6.4 ± 2.2), followed closely by astrocytes (5.5 ± 2.6), microglia/macrophages (4.5 ± 3.5), and oligodendrocyte precursor cells (3.2 ± 3.3). There was an increased proportion of anti-PAD2 positivity in the MS (19.8%; p=0.007) and PTLD groups (13.9%; p=0.057) relative to the healthy controls (5.7%), and these antibodies were not detected in NMO patients. Anti-PAD2 antibody levels inversely correlated with disease severity in people with MS (τ = -0.145, p = 0.02), and were highest in those with relapsing-remitting disease. In PTLD, anti-PAD2 levels inversely correlated with neurocognitive score (τ = -0.10, p=0.027), with difficulty focusing, memory changes, fatigue, and difficulty finding words contributing most strongly to the effect. Conclusion: PADI2 expression was observed in diverse regions and cells of the CNS, and anti- PAD2 autoantibodies were associated with less severe symptoms in patients with distinct neurologic diseases. These data suggest that anti-PAD2 antibodies may attenuate inflammation in diseases of different etiologies, which are united by high PADI2 expression in the target tissue.